THE CORRELATION BETWEEN LEARNING OUTCOMES OF PLANNING DRAWING COURSE AND STUDENTS’ INTEREST IN DRAWING WITH THE AUTOCAD PROGRAM FOR STUDENT OF BUILDING ENGINEERING EDUCATION PROGRAM OF STATE UNIVERSITY OF PADANG - 460-468 , Beny Setiawan (Universitas Negeri Padang, 2014)
ABSTRACT This research aimed to reveal the correlation between learning outcomes of Planning Drawings Course and students’ interest in drawing with the AutoCAD program. Preliminary observation showed that some students still use the AutoCAD program to draw and learn to master it, while some rarely use in their daily task afterward. This is a correlational research, the population is 115 students of Building Engineering Education program from two entrance years (2009 and 2010) that already took the Planning Drawing Course and received their result. Sample collection technique is Accidental Sampling with sample size of 30 students. Primary data were gained by using questionnaire. The analysis result showed that there is a correlation between learning outcomes of Planning Drawings Course and students’ interest in drawing with the AutoCAD program. The correlation is on medium level and the learning outcomes of Planning Drawings Course affect the students’ interest by 22,7%. Key Words: Learning outcomes, students’ interest, drawing with AutoCAD program